Validity and reliability of two-dimensional video-based assessment to measure joint angles during running: A systematic review and meta-analysis - Leporace, G.; Metsavaht, L.; Gonzalez, F. F.; de Jesus, F. A.; Machado, M.; Guadagnin, E. C.; Gomes-Neto, M. (Journal of Biomechanics, 2023)
Two-dimensional video analysis systems (2DVAS) are commonly used by clinicians and researchers to determine angles during running. The aim of this systematic review (PROSPERO: CRD42022322798) was to synthesize the literature on the criterion validity and reliability of 2DVAS for measuring angles during running compared to three-dimensional motion analysis systems (3DMAS). We searched for articles on MEDLINE/Pubmed, EMBASE, SciELO, and LILACS up to October/2022. We included studies that evaluated the validity of 2DVAS (when compared to 3DMAS) and/or the reliability of 2DVAS measurements of lower limb and trunk angles during running. Qualitative and quantitative analyses were performed. Seven hundred and five studies were found and 17 were included. Ten studies analysed criterion validity between 2DVAS and 3DMAS and the results ranged from poor to excellent, with most of the parameters assessed presenting poor or moderate validity. Inter-rater reliability of 2DVAS was assessed in nine studies and most of the parameters investigated had good to excellent reliability. Intra-rater reliability (between-day processing) of angular running parameters - investigated in ten studies - was considered excellent for most of the parameters analysed. Inter-session reliability was assessed in three studies and was defined as good or excellent for most of the variables assessed. 2DVAS is a reliable method for measuring joint angles during running. However, the validity of 2DVAS compared to 3DMAS ranges from low to moderate for most running parameters. Therefore, based on the available evidence, caution should be taken when applying 2DVAS, particularly for frontal and transverse plane angles.